Peran Motivasi Kerja Terhadap Hubungan Beban Kerja dan Kepuasan Kerja Guru: Sebuah Tinjauan Literatur Siistematis - Rivaldo Juliansyah; Mubiar Agustin; Eka Sakti Yudha (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Teachers frequently encounter heavy workloads, which can reduce job satisfaction. While various research have looked at this link, the function of job motivation as a deciding factor has not been thoroughly investigated. This systematic literature review seeks to investigate how motivation of work affects the relationship between workload with job satisfaction in teachers. Using the PRISMA framework, a thorough search was undertaken across major academic databases such as Crossref, Semantic Scholar, and Google Scholar, focused on publications published between 2015 and 2025. Inclusion criteria were peer-reviewed publications on motivation, workload, and job satisfaction in the context of school teacher. A total of 12 relevant studies were examined thematically. The data show that a high workload typically affects job satisfaction, although this impact can be mitigated or modulated by internal and extrinsic motivating variables. Teachers with higher levels of intrinsic motivation were more tolerant to workload-related stress and reported higher levels of satisfaction. This review emphasizes the necessity of improving motivating tactics in educational institutions in order to increase teacher well-being. More study is needed to investigate contextual variables including school culture and teacher tenure.